The Effect of Drug Users on Periodontal Health : Literature Review - Edi Karyadi; Ade Ismail Abdul Kodir; Nadia Fairuz Zahiro; Aulia Azizah Vidya Bouty (Odonto : Dental Journal, 2023)
Background: Drug trafficking in the world affects the country and spread to all levels of Indonesian society. Methamphetamine, marijuana, and heroin are the most commonly abused drugs. Drugs cause a lot of bad effects, including the oral cavity. Results of Health Research on the Impact of Drug Abuse in 2019, as many as 64.1% of them experienced dental problems and 60.1% of oral cavity disorders. The risk of periodontal disease in drug users is higher than non-users. Objective: To determine the effect of the use of methamphetamine, marijuana, and heroin and the most influential drug users on the health of periodontal tissues. Methods: Using secondary data obtained through several e-databases, that are Pubmed Central (PMC), SpringerLink, and ResearchGate based on keywords and a predetermined time span. Discussion: Periodontal disease in drug users is related to xerostomia, oral hygiene, and immunosuppression. The high accumulation of calculus and plaque in drug users due to their low awareness of maintaining oral health and impaired motor function that makes it difficult for a person to clean his oral cavity. Comparison of Bleeding on Probing (BOP) and Clinical Attachment Loss (CAL) values were used as the main variables to show the parameters of periodontal tissue inflammation in each type of drug (methamphetamine, marijuana, and heroin). Conclusion: There was an effect of methamphetamine, marijuana, and heroin on the health of periodontal tissues including gingivitis and periodontitis. The heroin used by intravenous injection had the most effect on periodontal tissue health compared to methamphetamine and marijuana.